Haemorrhagic thiamine deficient encephalopathy following prolonged parenteral nutrition. - Vortmeyer, A O (1992)
Neuropathological examination of three patients who were maintained on parenteral nutrition without substitution of thiamine demonstrated an acute haemorrhagic encephalopathy. The lesions differed substantially from the classic features of thiamine deficient encephalopathy regarding the histopathological alterations and the topographical distribution. The extreme rapidity of thiamine deprivation may have been responsible for the abrupt clinical onset of the disease and the intensity of the morphological alterations.